Investigation of Wilting and Decay Factors of Cucumber at Greenhouses (Case Study: in Kohgiluyeh-va-Boyerahmad, Iran) - Keshavarz, Kavoos; mirinejad, Shahab (Asian Journal of Biological and Life Sciences)
In order to identify the wilting and decay factors of cucumbers at greenhouses in Kohgiluyeh-va-Boyerahmad, a number of samples were taken of slow-growing plants with general yellowing, necrotic and chlorotic leaves, withered farm bushes, and cucumber greenhouses during 2011¬2012. After transferring the samples to the laboratory, the pathogens were immediately isolated and eliminated in the laboratory. The infected root and crown samples were disinfected and then cultured on a PDA medium. They were identified after purification through to the hyphal tip technique. The results showed that most infection in greenhouses was associated with downy mildew on cucumber caused by pseudoperenospora cubensis. The second fungus factor leading to leaf necrosis was detected to be a cucumbers powdery mildew fungus known as Erisiphe cichoracerum. Based on macroscopic and microscopic observations and confirmation on pathogenicity of the fungi, the necrosis of the plant and damping-off was associated with Pythium and Phytophthora.
Keywords: Cucumber; Identification; Kohgiluyeh-va-Boyer-Ahmad; Pseudoperenospora cubensis; Wilting